Atomic layer deposited films of Al2O3 on fluorine-doped tin oxide electrodes: stability and barrier properties - Krýsová, Hana; Neumann-Spallart, Michael; Tarábková, Hana; Janda, Pavel; Kavan, Ladislav; Krýsa, Josef (Beilstein Journal of Nanotechnology, 2021)
Al2O3 layers were deposited onto electrodes by atomic layer deposition. Solubility and electron-transport blocking were tested. Films deposited onto fluorine-doped tin oxide (FTO, F:SnO2/glass) substrates blocked electron transfer to redox couples (ferricyanide/ferrocyanide) in aqueous media. However, these films were rapidly dissolved in 1 M NaOH (≈100 nm/h). The dissolution was slower in 1 M H2SO4 (1 nm/h) but after 24 h the blocking behaviour was entirely lost. The optimal stability was reached at pH 7.2 where no changes were found up to 24 h and even after 168 h of exposure the changes in the blocking behaviour were still minimal. This behaviour was also observed for protection against direct reduction of FTO.
Keywords: Al2O3; atomic layer deposition (ALD); barrier properties; corrosion; electrochemistry; FTO

(untitled) - George, S. M. (Chem. Rev., 2010)

(untitled) - Krýsa, J.; Němečková, A.; Zlámal, M.; Kotrla, T.; Baudys, M.; Kment, Š.; Hubička, Z.; Neumann-Spallart, M. (J. Photochem. Photobiol., A, 2018)

(untitled) - Krýsa, J.; Imrich, T.; Paušová, Š.; Krýsová, H.; Neumann-Spallart, M. (Catal. Today, 2019)

(untitled) - Moehl, T.; Suh, J.; Sévery, L.; Wick-Joliat, R.; Tilley, S. D. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Imrich, T.; Zazpe, R.; Krýsová, H.; Paušová, Š.; Dvořák, F.; Rodriguez-Pereira, J.; Michalicka, J.; Man, O.; Macak, J. M.; Neumann-Spallart, M.; Krýsa, J. (J. Photochem. Photobiol., A)
under revision.

(untitled) - Li, C.; Wang, T.; Luo, Z.; Zhang, D.; Gong, J. (Chem. Commun., 2015)

(untitled) - Cheng, Q.; Benipal, M. K.; Liu, Q.; Wang, X.; Crozier, P. A.; Chan, C. K.; Nemanich, R. J. (ACS Appl. Mater. Interfaces, 2017)

Atlas d’Équilibres Électrochimiques - Pourbaix, M. (Gauthier-Villars et Cie., 1963)

(untitled) - Heyrovský, J. (J. Chem. Soc., Trans., 1920)

(untitled) - Daubert, J. S.; Hill, G. T.; Gotsch, H. N.; Gremaud, A. P.; Ovental, J. S.; Williams, P. S.; Oldham, C. J.; Parsons, G. N. (ACS Appl. Mater. Interfaces, 2017)

(untitled) - Singh, A. K.; Adstedt, K.; Brown, B.; Singh, P. M.; Graham, S. (ACS Appl. Mater. Interfaces, 2019)

(untitled) - Correa, G. C.; Bao, B.; Strandwitz, N. C. (ACS Appl. Mater. Interfaces, 2015)

(untitled) - Broas, M.; Kanninen, O.; Vuorinen, V.; Tilli, M.; Paulasto-Kröckel, M. (ACS Omega, 2017)

(untitled) - Le Formal, F.; Tétreault, N.; Cornuz, M.; Moehl, T.; Grätzel, M.; Sivula, K. (Chem. Sci., 2011)

(untitled) - Kment, S.; Hubicka, Z.; Krysa, J.; Sekora, D.; Zlamal, M.; Olejnicek, J.; Cada, M.; Ksirova, P.; Remes, Z.; Schmuki, P.; Schubert, E.; Zboril, R. (Appl. Catal., B, 2015)

(untitled) - Kafizas, A.; Xing, X.; Selim, S.; Mesa, C. A.; Ma, Y.; Burgess, C.; McLachlan, M. A.; Durrant, J. R. (Catal. Today, 2019)

(untitled) - Miikkulainen, V.; Leskelä, M.; Ritala, M.; Puurunen, R. L. (J. Appl. Phys., 2013)

(untitled) - Kavan, L.; Tétreault, N.; Moehl, T.; Grätzel, M. (J. Phys. Chem. C, 2014)

(untitled) - Kavan, L.; Steier, L.; Grätzel, M. (J. Phys. Chem. C, 2016)

(untitled) - Krýsová, H.; Krýsa, J.; Kavan, L. (Beilstein J. Nanotechnol., 2018)

(untitled) - Kavan, L. (Curr. Opin. Electrochem., 2018)

(untitled) - Palomares, E.; Clifford, J. N.; Haque, S. A.; Lutz, T.; Durrant, J. R. (J. Am. Chem. Soc., 2003)

(untitled) - Kavan, L.; Živcová, Z. V.; Hubík, P.; Arora, N.; Dar, M. I.; Zakeeruddin, S. M.; Grätzel, M. (ACS Appl. Energy Mater., 2019)

Powder Diffraction File Alphabetic PDF-2 Data Base (International Center of Diffraction Data, 1994)